Synthesis of (R)-selegiline via hydrolytic kinetic resolution - Kondekar, Nagendra B.; Kumar, Pradeep (Synthetic Communications, 2011)
[image omitted] A short and enantioselective formal synthesis of (R)-selegiline has been achieved using Jacobsen's hydrolytic kinetic resolution (HKR) of phenyl propylene oxide.
Keywords: Cobalt-based chiral salen complex; Hydrolytic kinetic resolution; MAO inhibitors; phenyl propylene oxide; selegiline